Markets, morals, politics jealousy of trade and the history of political thought - Kapossy, Bela, 1965-; Nakhimovsky, Isaac, 1979-; Reinert, Sophus A.; Whatmore, Richard (Harvard University Press, 2018)
When Istvan Hont died in 2013, the world lost a giant of intellectual history. A leader of the Cambridge School of Political Thought, Hont argued passionately for a global-historical approach to political ideas. To better understand the development of liberalism, he looked not only to the works of great thinkers but also to their reception and use amid revolution and interstate competition. His innovative program of study culminated in the landmark 2005 book Jealousy of Trade, which explores the birth of economic nationalism and other social effects of expanding eighteenth-century markets. Markets, Morals, and Politics brings together a celebrated cast of Hont's contemporaries to assess his influence, ideas and methods. Richard Tuck, John Pocock, John Dunn, Raymond Geuss, Gareth Stedman Jones, Michael Sonenscher, John Robertson, Keith Tribe, Pasquale Pasquino, and Peter N. Miller contribute original essays on themes Hont treated with penetrating insight.--